2011
DOI: 10.4049/jimmunol.1001950
|View full text |Cite
|
Sign up to set email alerts
|

IFN Regulatory Factor 8 Restricts the Size of the Marginal Zone and Follicular B Cell Pools

Abstract: Transcriptional control of marginal zone (MZ) and follicular (FO) B cell development remains incompletely understood. The transcription factor, IFN regulatory factor (IRF)8, is known to play important roles in the differentiation of early B cells. In this article, we demonstrate that IRF8 is also required for normal development of MZ and FO B cells. Mice with a conventional knockout of Irf8 (IRF8–/–) or a point mutation in the IRF association domain of IRF8 had increased numbers of MZ B cells. To determine the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 48 publications
4
81
0
Order By: Relevance
“…1C), which do not express IRF8 (35). As noted previously with Irf8 −/− normal background mice (36,37), IRF8-deficient NZB mice also showed expansion of marginal zone and CD21 low CD23 + follicular and transitional B cells, but total B-cell and T-cell numbers were unchanged (data not shown).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…1C), which do not express IRF8 (35). As noted previously with Irf8 −/− normal background mice (36,37), IRF8-deficient NZB mice also showed expansion of marginal zone and CD21 low CD23 + follicular and transitional B cells, but total B-cell and T-cell numbers were unchanged (data not shown).…”
Section: Resultssupporting
confidence: 52%
“…However, as reported previously (37) and reproduced here with IRF8-deficient NZB mice, humoral responses to exogenous antigens remain unmodified. Furthermore, we have shown that Irf8 −/− B cells mounted normal in vitro responses to TLR7 and TLR9 ligands, which could be enhanced with IFN-α.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…12,15,24 However, compared with other hematologic malignancies, like diffuse large B-cell lymphoma (DLBCL), chronic lymphocytic leukemia, acute lymphoblastic anemia, or multiple myeloma, the current understanding of the incidence of recurrent gene mutations and the interplay of gene mutations and aCNA/ LOH and cnLOH in FL is in its early stages and largely incomplete. 3,[25][26][27][28][29][30][31][32][33][34][35] The discovery of genes mutated in various forms of cancer has further advanced our understanding of the specific pathogenetic mechanisms that operate in cancer cell subtypes. Recently, as a result of the study of DLBCL, 2 novel high-frequency mutated genes (MLL2 and CREBBP) in non-Hodgkin lymphoma (NHL) were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of B lineage cells showed that IRF8 contributes to a series of transcriptional networks affecting the earliest stages of lineage commitment and specification in the bone marrow (12), rearrangements at the immunoglobulin (Ig) locus (13), and distribution of mature cells into splenic B cell subcompartments (14). IRF8 was shown to exert its influences on the germinal center (GC) reaction, class switch recombination, and plasma cell development through partnering with PU.1 and IRF4 to promote the activation of Aicda and Bcl6, genes central to the maintenance of the B cell program, while repressing genes such as Prdm1 that promote terminal differentiation (15,16).…”
mentioning
confidence: 99%